ANALISIS PENGARUH SUDUT KAMPUH DAN KUAT ARUS PENGELASAN TERHADAP KEKUATAN TARIK HASIL PENGELASAN SHIELDED ARC WELDING (SAW) - Rahman Hakim, Arif; Hasibuan, Fardin (Fakultas Teknik, Universitas Riau Kepulauan, 2024)
This research aims to study the effect of seam angle and welding current on the tensile strength, toughness, and hardness of the welding results. The material studied was low alloy steel containing levels of C = 0.098 %, Si = 0.228 %, Mn = 1.489 %, S = 0.007 %, P = 0.014 %, Ni = 0.151 %, Nb = 0.06, Cr = 0.085%, V=0.05%, W=0.05 %, Ti=0.01%. Welding is carried out with varying currents of 600A to 630A, using reverse polarity DC SAW welding, and alternating current AC with ESAB OK 12.32 electrodes with a diameter of 4.0 mm. DC current with reverse polarity, namely the electrode holder is connected to the positive pole and the parent metal is connected to the negative pole. The type of seam used is a single V seam with angles of 55o and 60o. Next, the specimens will be tested for tensile strength, toughness, hardness, and microphotography. The test results showed that the highest tensile strength of the welded joint occurred in the group of specimens welded with a current strength of 600A and a seam with an angle of 55o. The microstructure looks tighter compared to the microstructure of specimens welded with other variations of welding current. According to the results of this research, it can be concluded that with variations in the welding current, structural changes occur due to cooling, which affects the strength of the material, namely an increase in the raw materials